A preliminary study of selected neo-Ilonggos an immigration history - Torio, Tita; Padilla, Melanie J. (2007)
This paper documents the lives of neo-Ilonggos, foreign nationals who have established residence for several years in Iloilo City. Through oral history and library research, the study found out that neo-Ilonggos settled in the city because of marriage, business opportunities, religious mission, job offer and regime change in place of origin. Despite some problems, they have established links with the locals and managed to surmount difficulties. Although there are no ethnic enclaves here, the presence of foreign nationals not as tourists but as residents has, to some extent, contributed to the development of cultural diversity or multiculturalism of Iloilo City.